Not as easy as π: An insertional residue does not explain the π‐helix gain‐of‐function in two‐component FMN reductases. (15th November 2018) - McFarlane, Jeffrey S.; Hagen, Richard A.; Chilton, Annemarie S.; Forbes, Dianna L.; Lamb, Audrey L.; Ellis, Holly R.
Abstract: The π‐helix located at the tetramer interface of two‐component FMN‐dependent reductases contributes to the structural divergence from canonical FMN‐bound reductases within the NADPH:FMN reductase family. The π‐helix in the SsuE FMN‐dependent reductase of the alkanesulfonate monooxygenase system has been proposed to be generated by the insertion of a Tyr residue in the conserved α4‐helix. Variants of Tyr118 were generated, and their X‐ray crystal structures determined, to evaluate how these alterations affect the structural integrity of the π‐helix. The structure of the Y118A SsuE π‐helix was converted to an α‐helix, similar to the FMN‐bound members of the NADPH:FMN reductase family. Although the π‐helix was altered, the FMN binding region remained unchanged. Conversely, deletion of Tyr118 disrupted the secondary structural properties of the π‐helix, generating a random coil region in the middle of helix 4. Both the Y118A and Δ118 SsuE SsuE variants crystallize as a dimer. The MsuE FMN reductase involved in the desulfonation of methanesulfonates is structurally similar to SsuE, but the π‐helix contains a His insertional residue. Exchanging the π‐helix insertional residue of each enzyme did not result in equivalent kinetic properties. Structure‐based sequence analysis further demonstrated the presence of a similar Tyr residue in an FMN‐bound reductase in the NADPH:FMN reductase family that is not sufficient to generate a π‐helix. Results from the structural and functional studies of the FMN‐dependent reductases suggest that the insertional residue alone is not solely responsible for generating the π‐helix, and additional structural adaptions occur to provide the altered gain of function. Abstract : PDB Code(s):6DQI, 6DQP, 6DQO